2011
DOI: 10.2319/030911-173.1
|View full text |Cite
|
Sign up to set email alerts
|

Localization of osteopontin and osterix in periodontal tissue during orthodontic tooth movement in rats

Abstract: Objective: To evaluate the localization of osteopontin (OPN) and osterix in periodontal tissue during experimental tooth movement with heavy force in rats. Materials and Methods: Nickel-titanium closed-coil springs were used to create a 100 g mesial force to the maxillary first molars. On days 3, 7, 10, and 14 after force application, histological changes in periodontium were examined by immunohistochemistry using proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 24 publications
1
24
0
Order By: Relevance
“…The Osterix ( Osx )- Cre line has been used to selectively delete floxed alleles in committed osteoblasts and odontoblasts [30, 31], though the spatiotemporal expression of Osx in the wider periodontium has not been completely resolved [32-34]. While the Osx-Cre transgene has been reported to cause delayed or defective skeletal and craniofacial mineralization resulting from Osterix loss-of-function [35-37], studies including analysis of molar teeth have not identified similar dental defects [30, 38, 39].…”
Section: Resultsmentioning
confidence: 99%
“…The Osterix ( Osx )- Cre line has been used to selectively delete floxed alleles in committed osteoblasts and odontoblasts [30, 31], though the spatiotemporal expression of Osx in the wider periodontium has not been completely resolved [32-34]. While the Osx-Cre transgene has been reported to cause delayed or defective skeletal and craniofacial mineralization resulting from Osterix loss-of-function [35-37], studies including analysis of molar teeth have not identified similar dental defects [30, 38, 39].…”
Section: Resultsmentioning
confidence: 99%
“…Animal experiments have demonstrated that continuous tensile strain generated by orthodontic appliances also upregulates osteogenic markers in PDL during orthodontic tooth movement (Kawarizadeh et al, 2005; Kim et al, 2012; Watanabe et al, 2008). Therefore, our device induces similar biological effects in the cells.…”
Section: Discussionmentioning
confidence: 99%
“…SPP1 is thought to promote or regulate the adhesion, attachment, and spreading of osteoclasts to the bone surface during bone resorption (Standal et al, 2004). Previous studies have demonstrated that mechanical stress-induced expression of SPP1 is mostly composed of, or is present in, almost all osteocytes and in some osteoblasts and bone-lining cells at the resorption site in the early stage of experimental tooth movement (Terai et al, 1999;Kim et al, 2012). Therefore, we chose SPP1 as the major indicators to observe the osteogenic differentiation of hPDLCs under CTS.…”
mentioning
confidence: 99%